Implementation of a Verbal Compiler: The Need to Develop Audio Language to Keep Pace with Rapid Development becomes a Necessity (Global Journal of Human-Social Science, 2020)
Abstract not found
Keywords: artificial intelligence; speech recognition; compiler construction; audio programming language